2011
DOI: 10.1038/bjc.2011.280
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of modified FOLFOX6 and erlotinib in patients with metastatic or advanced adenocarcinoma of the oesophagus and gastro-oesophageal junction

Abstract: Background:There is increased recognition that cancers of the upper GI tract comprise distinct epidemiological and molecular entities. Erlotinib has shown activity in patients with adenocarcinoma of the oesophagus/gastro-oesophageal junction (GEJ), but not in distal gastric cancer. mFOLFOX6 is one of several active regimens used to treat adenocarcinoma of the Eso/GEJ. This study evaluates the efficacy and safety of mFOLFOX6 and erlotinib in patients with metastatic or advanced Eso/GEJ cancers.Methods:Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 38 publications
2
31
0
1
Order By: Relevance
“…In addition, laptinib showed a synergistic effect with trastuzumab in vitro and in vivo to inhibit HER2 amplified human gastric cancer cells and animal model [23]. Clinical phase II trial of lapatinib as first line therapy in patients with advanced or metastatic cancer showed well tolerated, which will be another potential drug to target HER2 receptors [59].…”
Section: Gastricmentioning
confidence: 99%
“…In addition, laptinib showed a synergistic effect with trastuzumab in vitro and in vivo to inhibit HER2 amplified human gastric cancer cells and animal model [23]. Clinical phase II trial of lapatinib as first line therapy in patients with advanced or metastatic cancer showed well tolerated, which will be another potential drug to target HER2 receptors [59].…”
Section: Gastricmentioning
confidence: 99%
“…En un ensayo de fase II se encontró que el erlotinib era activo en pacientes con cáncer gastroesofágico, pero no se obtuvo buena respuesta en pacientes con CG 73 (Tabla 2). En un ensayo de fase II se administró una combinación de erlotinib, oxaliplatino, leucovorina y 5-fluorouracilo (5FU) a pacientes sin tratamiento previo con cáncer de esófago avanzado o metastásico y cáncer gastroesofágico; los resultados fueron similares a los reportadas previamente 74 (Tabla 2). El gefitinib fue aprobado por la FDA para el tratamiento del cáncer de pulmón de células no microcíti-cas avanzado 54 .…”
Section: Inhibidores Her1unclassified
“…One trial suggested that GEJAs were more likely to respond to erlotinib than gastric cancers [32]; in another trial, responses were seen almost exclusively in SCC as compared to AD [33]. A possible explanation is that KRAS and EGFR mutations are uncommon [31][32][33][34][35] and thus not predictive of response to TKI in esophageal cancer. In conclusion, the results were very modest at best for these agents in a metastatic setting.…”
Section: Targeting the Epidermal Growth Factor Familymentioning
confidence: 99%
“…Stable disease and RR generally were in the magnitude of 10 %, except in one trial [31]. One trial suggested that GEJAs were more likely to respond to erlotinib than gastric cancers [32]; in another trial, responses were seen almost exclusively in SCC as compared to AD [33].…”
Section: Targeting the Epidermal Growth Factor Familymentioning
confidence: 99%